PENGARUH HARGA, FASILITAS DAN KUALITAS PELAYANAN TERHADAP MINAT BERKUNJUNG KEMBALI PADA HOTEL CHANTI SEMARANG 2020 - Henry Casandra Gultom; Ronal Dino Kuncoro Sakti; Heri Prabowo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
This study aims to determine the effect of price, facilities and service quality on interest inreturning to Chanti Hotel Semarang. This research was conducted on visitors to Hotel ChantiSemarang. The population in this study were all visitors to the Chanti Hotel Semarang in 2019/2020,the sample in this study was 100 respondents. In collecting research data using a Likert scale with 5assessment criteria and to measure 24 statement items. The sampling technique in this researchuses a type of probability sampling. The data analysis technique is linear regression analysis. Haslianalysis states that price affects the interest to return partially, facilities do not have a partial effectand service quality greatly affects the interest in returning to visit.